Growth‐Induced Strain in Chemical Vapor Deposited Monolayer MoS2: Experimental and Theoretical Investigation. Issue 17 (13th April 2017) - Kataria, Satender; Wagner, Stefan; Cusati, Teresa; Fortunelli, Alessandro; Iannaccone, Giuseppe; Pandey, Himadri; Fiori, Gianluca; Lemme, Max C.
Abstract : Monolayer molybdenum disulfide (MoS2 ) is a promising 2D material for nanoelectronic and optoelectronic applications. The large‐area growth of MoS2 has been demonstrated using chemical vapor deposition (CVD) in a wide range of deposition temperatures from 600 to 1000 °C. However, a direct comparison of growth parameters and resulting material properties has not been made so far. Here, a systematic experimental and theoretical investigation of optical properties of monolayer MoS2 grown at different temperatures is presented. Micro‐Raman and photoluminescence (PL) studies reveal observable inhomogeneities in optical properties of the as‐grown single crystalline grains of MoS2 . Close examination of the Raman and PL features clearly indicate that growth‐induced strain is the main source of distinct optical properties. Density functional theory calculations are carried out to describe the interaction of growing MoS2 layers with the growth substrate as the origin of strain. This work explains the variation of bandgap energies of CVD‐grown monolayer MoS2, extracted using PL spectroscopy, as a function of deposition temperature. The methodology has general applicability to model and predict the influence of growth conditions on strain in 2D materials. Abstract : Raman spectroscopy and photoluminescence data of chemical vapor deposited single‐layer MoS2 are found to be dependent on the growth temperature. Experiments and simulations reveal that the observed changes in optical properties can be attributed to growth‐induced strain via substrate interactions.